2016
DOI: 10.11621/pir.2016.0104
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural relations in Kabardino-Balkaria: Does integration always lead to subjective well-being?

Abstract: This article examines intercultural relations in Kabardino-Balkaria. Among a great number of ethnic groups living in Kabardino-Balkaria, Kabardians and Balkars are one of the largest (they are so-called titular ethnic groups). Russians are the second largest of the ethnic groups after Kabardians. We report here the results of an empirical study of the intercultural relations, mutual acculturation, and adaptation of Kabardians and Balkars (N = 285) and Russians (N = 249). Specifically, we examine the relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…These findings are consistent with results obtained in the Kabardino-Balkar Republic (KBR), Russia, by Z. Lepshokova and A. Tatarko (2016). The authors explained this phenomenon through the group-threat theory (Bobo, 1999) stating that when a minority group challenges the social position of a majority group by maintaining their own culture, the majority group feels threatened and prefers the assimilation of the minority (Davies, Steele, & Markus, 2008;Tip et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with results obtained in the Kabardino-Balkar Republic (KBR), Russia, by Z. Lepshokova and A. Tatarko (2016). The authors explained this phenomenon through the group-threat theory (Bobo, 1999) stating that when a minority group challenges the social position of a majority group by maintaining their own culture, the majority group feels threatened and prefers the assimilation of the minority (Davies, Steele, & Markus, 2008;Tip et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies it was found that preference for assimilation is positively related to life satisfaction (Lepshokova & Tatarko, 2016;Ryabichenko & Lebedeva, 2016) and sociocultural adaptation, but negatively related to selfesteem Ryabichenko & Lebedeva, 2016). Based on the above, we formulated the following hypothesis:…”
Section: Introductionmentioning
confidence: 96%